Faktor-Faktor Yang Mempengaruhi Kepuasan Wisatawan Berkunjung Ke Lokasi Wisata Cimory - JAKARIAS RIAN RIMPASA; Lasmono Tri Sunaryanto (LPPM Universitas Al Asyariah Mandar, 2023)
Tourist satisfaction in visiting Cimory Bawen tourist sites needs to be increased by providing tourist attractions, good service quality and product quality from these tours. The purpose of this study was to determine the factors that influence the satisfaction of tourists visiting Cimory Bawen tourist sites. This research was conducted at the Cimory Bawen Tourism Site, Jalan Raya Soekarno Hatta, Km.30, Bergas, Jatijajar, Semarang. This type of research is a quantitative research. Source of data using primary data. Sampling technique with accidental sampling. The number of samples is 40 people. Data analysis method using classical assumption test, multiple linear regression analysis, and hypothesis testing with simultaneous test (F-test) and partial test (t-test) using SPSS software. The results showed that attractiveness, service quality and product quality affect the satisfaction of tourists visiting Cimory Bawen tourist sites.